Root cause failure analysis - Mobley, R. Keith, 1943- (Newnes, 1999)
Root Cause Failure Analysis provides the concepts for performing industrial troubleshooting investigations. It describes the methodology to perform Root Cause Failure Analysis (RCFA), a topic in maintenance engineering. It also includes equipment design and troubleshooting guidelines, which are used to perform RCFA on machinery found in most production facilities.
Keywords: Plant maintenance.; System failures (Engineering); elektronické knihy; electronic books